Polarized emission and mechanofluorochromism of benzothiadiazole based chromophores oriented by rubbing. (August 2022) - Squeo, Benedetta Maria; Bertini, Fabio; Scavia, Guido; Uslenghi, Michela; Fois, Ettore; Pasini, Mariacecilia; Botta, Chiara
Abstract: Mechanofluorochromic (MFC) organic chromophores are a versatile class of materials whose applications include mechanical sensors, security inks and optical data storage devices. Molecules with Liquid-Crystal (LC) properties can be easily oriented by several techniques providing films with highly anisotropic properties. Thin organic films with polarized emission properties represent ideal materials for OLED applications requiring polarized emission, such as backlights for commercial LC displays. We have synthetized molecules and polymers composed of a rod-like rigid core based on the highly emissive benzothiadiazole moiety and flexible chains to produce oriented films with polarized emission in the green/yellow and red regions. Films oriented by mechanical rubbing display absorption anisotropies and emission polarization up to 5. Beside orienting the molecular axis of the molecules, mechanical rubbing induces a conformational relaxation towards their most stable and elongated state thanks to the arrangement of the terminal alcoxy chains. According to the chromophore molecular structure, the oriented films display either stable (polymers) or mechano-sensitive (molecules) polarized emissions with fluorescence efficiencies up to 1. In the molecular blends highly sensitive polarized mechanofluorochromism, originating from the peculiar modulation of the energy transfer efficiency directly in bulk, opens to smart sensors able to detect the direction of application of a mechanical stress. Graphical abstract: Highly anisotropic rubbing oriented films of benzothiadiazole based chromophores show sensitive polarized MechanoFluoroChromism induced by FRET modulation. Image 1 Highlights: Highly anisotropic rubbing oriented thin films with bright polarized fluorescence. Benzothiadiazole based materials from molecules to poly(rod-coil) polymers. Oriented MechanoFluoroChromic organic materials for smart mechanical sensors. Polarized reversible MechanoFluoroChromism induced by FRET modulation. Molecular conformational relaxation induced by mechanical rubbing.